Genome-wide regulation of electro-acupuncture on the neural Stat5-loss-induced obese mice. - Shu-Ping Fu; Hao Hong; Sheng-Feng Lu; Chen-Jun Hu; Hou-Xi Xu; Qian Li; Mei-Ling Yu; Chen Ou; Jian-Zhong Meng; Tian-Lin Wang; Lothar Hennighausen; Bing-Mei Zhu (PLoS ONE)
Acupuncture is reported to be effective in treating obesity related illnesses, but its mechanism is still unclear. To investigate this mechanism we applied electro-acupuncture (EA) in a mouse model of obesity and used RNA-seq to identify molecular consequences. Deletion of the transcription factor STAT5 from neurons (Stat5NKO) led to obesity. Acupuncture, in turn, reduced body weight and the ratio of epididymal white adipose tissue (Epi-WAT) to body weight, and it also decreased plasma concentrations of glucose, triglyceride, and cholesterol. In addition, EA increased cold endurance of Stat5NKO obese mice. EA reversed altered gene expressions in the hypothalamus and Epi-WAT, especially in the hypothalamus in Stat5NKO obese mice. This study provides, for the first time, insight into genomic networks of obesity and their modulation by electro-acupuncture, which in turn reveals potential mechanisms that explain acupuncture-induced weight-loss.